City of Baghdad Analysis of the mechanisms of economic action in the development and development (Journal of Planner and Development, 2008)
The economy of a city has an important role not only in its establishment but also in its development. This is quite clear in the city of Baghdad throughout its history since its building in 762 A.D. In addition, most of its problems that the city is suffering from are basically related to not giving enough importance to the economic factors in the master planning of Baghdad since 1950’s. This may explain the failiars of master plans in dealing with the actual population growth and the city’s inability to absorb such increases and interrelated and diverse activities which are negatively reflected on the economic variables particularly the effect on the land values, and the strong competitions amongst the land uses without previous economic regulation, such will require good flexibility in dealing with the land uses in time and location, not only within the city but also in its regional dimension. Such consideration was apparent in the comprehensive Development plan study for the city of Baghdad. However, this plan has not been treated with the importance it deserve in its application, and so a great many unauthorized and wrong land uses hove sprang up within the city, these have resulted in a negative way its economic operation as well as on deterioration of its services especially since 1990’s . All this has leaded this researcher to draw planning economic proposals on how Baghdad should be planned.